Aerodynamic design of a double slotted morphed flap airfoil– a numerical study - Shahrokhi, S. S.; Taeibi Rahni, M.; Akbari, P. (Frontiers in Mechanical Engineering, 2024)
The objective of this study is to develop and simulate a double slotted morphed flap with the intention of reducing drag and enhancing lift, thereby leading to a smaller flap size and reduced weight. A flap was meticulously designed to accommodate conditions at Mach 0.2 and Reynolds numbers of 4.7×10 6 .To conduct the simulation, ANSYS FLUENT flow solver and POINTWISE grid generator were utilized. The morphing technique employed involved adjusting both flap mean camber and flap slots, ensuring minimal flow interferences. By discretizing the flap mean camber line, various flap geometries were achieved. The findings reveal a significant enhancement in the airfoil's aerodynamic efficiency attributed to the implementation of the new flap design. The study shows that utilizing double-slotted morphing in the NACA 4412 airfoil at a 30° flap deflection angle increased the lift coefficient by 82% compared to the un-morphed state. A comparison of lift coefficients between this research and the NACA 4412 split flap at a 60° deflection angle indicates that the double-slotted morphing in the NACA 4412 airfoil at a smaller deflection angle of 30° results in a 14% higher maximum lift coefficient.